Bosnia and Herzegovina : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Banking Supervision and Corporate Governance. (IMF Staff Country Reports; Country Report ;, 2006)
Economic growth in Bosnia and Herzegovina (BiH) has been impressive with GDP. The dominance of foreign-owned bank subsidiaries has transformed the financial sector and altered the risks to financial stability. Reforms should focus on strengthening banking supervision and adapting it to the transformation of the financial system in line with recommendations in the Basel Core Principles (BCP) assessment. Although the insurance sector is too small to be systemically important, the unsettled conditions in the sector could weaken confidence in the financial system.